Space Funding and Geopolitical Competition: How Information Shapes Public Support - Sebastian Fehrler; Lars Hornuf; Daniel Vrankar (CESifo GmbH, 2025)
The space sector has remained central to geopolitics since the end of the Cold War, leading to an increase in national space spending worldwide. This study investigates how public support for space funding is influenced by information about (i) national space spending, (ii) the spending of geopolitical rivals, and (iii) the roles of private companies. We collected data from 2,135 citizens from the nine most important spacefaring nations. When informing them about their national space budgets, we find an increased willingness to increase their national space budget. However, information about high spending from rivals significantly reduces support for space budgets. When it comes to solving geopolitically relevant tasks, citizens show no preference for traditional space agencies over private companies, except in the US, where NASA receives stronger support than private firms. The findings serve as a caution to policymakers against using comparative rhetoric, as it may inadvertently reduce public support for space funding.
Keywords: C99; D83; F50; F51; H50; H56; 330; geopolitics; space race; contest theory; policy preferences; limited information; public economics